Islamic work ethics and employee’s task performance: The mediation role of affective commitment - Ali Ateeq; Mohammed Alzoraiki; Marwan Milhem; Mujeeb Al-Absy; Ranyia Ateeq (Problems and Perspectives in Management)
The study investigates the effect of Islamic work ethics on task performance. Further, it examines the mediating role of affective commitment on the relationship between Islamic work ethics and task performance. The study employed a random sampling method. Data were gathered via questionnaires distributed among 370 medical staff in the public healthcare facilities in the Kingdom of Bahrain, namely doctors, nurses, and pharmacists. The survey gathered demographic data from participants and assessed their perspectives on the relationship between Islamic work ethics and task performance and the mediation effect of affective commitment on that relationship. Data analysis using SPSS and SmartPLS4 software revealed a highly significant relationship between Islamic work ethics and task performance. Further, the results found that affective commitment significantly mediated the relationship between Islamic work ethics and task performance. The direct effect of Islamic work ethics on task performance is more substantial than an indirect impact of affective commitment. Therefore, Islamic work ethics play a useful role as an independent factor in increasing employee task performance among medical staff. The findings contribute to all stakeholders and policymakers who strive to strengthen the performance of employees in the Kingdom of Bahrain.